Grazing with bullets in Africa: Fulani herdsmen-community killings and state response in Nigeria - Bamidele, Seun (Acta criminologica, 2018)
Historically, Fulani herdsmen are known for peaceful conduct of their herding as they move from one region to another in search of pasture for their livestock. The wanton killing of people by Fulani herdsmen in many communities in Nigeria has become a security concern in a country which has had a series of violent conflicts in the past two decades. The incessant clashes between herdsmen and agriculturalists (farmers) are due to the Fulani herding their cattle through farmlands for grazing, which destroys crops and deprives farmers of high productivity resulting in loss of wealth. Climatic changes in the areas where the majority of the herdsmen are domiciled have made it necessary to look elsewhere for grazing land for their livestock. There have been reported cases of rape, vandalisation of properties, assault, theft and murder committed by herdsmen. The resolve to resort to the use of firearms and weapons to deter the herdsmen in areas where they are not welcome has become a challenge for policy makers and security agencies. This study examines the triggers, trends and patterns and implications of armed Fulani herdsmen, the hostility of communities to herdsmen invasion, and state responses to the killings between herdsmen and the host communities.